Pelatihan Kepemimpinan: From Organization to Become the Best Leader - Prasetyo, Johan Hendri; Wiharso, Gani; Fabrianto, Luky; Safitri, Rizky Ade (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
The community service activity holds a crucial urgency in raising awareness about the significant role of youth in village development, particularly in Ragunan District. By organizing the "Leadership Training: From Organization to Become The Best Leader" event, the primary aim is to provide a profound understanding of effective leadership for the younger generation, especially for the management of Karang Taruna RW 01 Ragunan. Through a series of leadership training and skill development, it is expected that participants can lead more effectively and actively contribute to the advancement of their villages. The targeted outcomes include the enhancement of quality and capacity among youth in leadership, innovation, and contribution to village development, as well as the establishment of strong networking and collaboration among youth in Ragunan District.